Wzory myślenia o profesji nauczycielskiej w tradycji pedeutologicznej = Teaching in the pedeutological tradition - thinking patterns - Bartkowiak, Edyta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article presents the origin of the teaching profession and the change in thinking about this occupation. The test describes a few theoretical approaches to the teacher as a tutor in the pedeutological thought: psychological approach, which demonstrates the personal and moral qualities of the teacher; competence approach focused on the teacher`s skills, duties and qualifications; and personalistic approach presenting the teacher as an artist who creates the masterpiece of education.
Keywords: nauczyciele; wychowawca; zawód nauczyciela; pedeutologia; osobowość; kompetencje; umiejętności zawodowe; powinności nauczycielskie; etyka; moralność; autorytet; teacher; tutor; profession; pedeutology; personality; competencies; professional skills; duties of a teacher; ethics; morality; authority